2002
DOI: 10.1207/s15324796abm2401_05
|View full text |Cite
|
Sign up to set email alerts
|

The ironson-woods spirituality/religiousness index is associated with long survival, health behaviors, less distress, and low cortisol in people with HIV/AIDS

Abstract: The purpose of this study was to determine the reliability and validity of an instrument that measures both spirituality and religiousness, to examine the relation between spirituality and religiousness and important health outcomes for people living with HIV and to examine the potential mediators of these relations. One aim was to determine whether subscales of spirituality, religiousness, or both would be independently related to long survival in people living with AIDS. The Ironson-Woods Spirituality/Religi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
187
3
7

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 272 publications
(210 citation statements)
references
References 31 publications
13
187
3
7
Order By: Relevance
“…These variables are spirituality, stigma, stress, patient satisfaction, and patient participation in decision-making. Studies show that people with HIV who are more spiritual report more positive health practices (Latkin et al 2002), more hope and social support (Ironson et al 2002), less affective or emotional distress (Ironson et al 2002;Sowell et al 2000), and fewer depressive symptoms (Coleman 2004;Sterk et al 2003). In contrast both stigma and stress have been noted to have negative effects on well being.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…These variables are spirituality, stigma, stress, patient satisfaction, and patient participation in decision-making. Studies show that people with HIV who are more spiritual report more positive health practices (Latkin et al 2002), more hope and social support (Ironson et al 2002), less affective or emotional distress (Ironson et al 2002;Sowell et al 2000), and fewer depressive symptoms (Coleman 2004;Sterk et al 2003). In contrast both stigma and stress have been noted to have negative effects on well being.…”
Section: Theoretical Perspectivementioning
confidence: 99%
“…The parent study established that spirituality/ religiousness is associated with long survival, health behaviors, more optimism, less distress and low cortisol in PLWH. 17 In a study in HIV-positive women, mainly African American, 92% reported that prayer was an important source for HIV medication decision-making, with 59% considering prayer more important than the physician, which created a sense of conflict for some. 43 Physicians may ask about the patient's spirituality/worldview as an aid in coping.…”
Section: Surrogate Markers-manymentioning
confidence: 99%
“…The study was conducted as a sub-study of the longitudinal parent study on the psychology of health and long survival with HIV/AIDS (Ironson et al, 2001;Ironson et al, 2002;Ironson et al, 2005a;Ironson et al, 2005b). The longitudinal study started in March 1997 and recruited a diverse paid-volunteer sample from AIDS-organizations, doctors' offices, and communityevents in southeast Florida.…”
Section: Study Population and Samplingmentioning
confidence: 99%